THE BRAZILIAN SOAP OPERA: FROM THE ORIGIN TO ITS CONSTITUTION AS A COMMUNICATIVE RESOURCE - Alves Marques, Francisco Claudio [UNESP]; Ribeiro, Rondinele Aparecido (Univ Fundacao Mineira Educacao & Cultura-fumec, 2017)
The soap opera is a very relevant genre of media fiction in Brazil, it has being constantly studied due to its ability to represent reality, serving as a cultural showcase. Introduced in the country in 1951, it can be said that the history of this genre is mingled with the own history of television in Brazil. The first soap operas were broadcast live, in non-daily format and with an alienating and evasive story; so the soap opera was disqualified by the reviews since then. However, the genre was disengaged from the essential characteristics of its Latin American matrix, becoming a largely problematizing narrative about the Brazilian reality. This article aims to discuss some of the considerations about soap opera origins, focusing on the hypothesis that it consists in a factual narrative about the nation and as a relevant communicative resource, as Lopes (2014) argues.
Keywords: Soap Opera; Mediatic Narrative; Investigation; Communicative Resource